The analysis of flow characteristics in multi-channel heat meter based on fluid structure model - 刘正刚 杜广生 刘丽萍 (Journal of hydrodynamics. Series B, 2015)
In this paper, a fluid structure interaction（FSI） model is used to study the internal flow field and the measurement performance of a multi-channel flow meter. The RNG k- ε turbulent model and the finite element model are used separately in the fluid domain and the structure domain to obtain the meter factor K and the deformation of the structure. The meter factor K of the flow meter is obtained through the FSI model at temperatures of 20 ℃, 50 ℃ and 80 ℃. The calculated results show the thermo expansion of the structure can significantly influence the measurement performance of the flow meter. The meter factor of the flow meter is also measured experimentally, and the comparison between the experimental results and the calculated results shows the validity of the fluid-structure interaction model. In order to reduce the measurement error, the meter factor K should be modified as the water temperature changes.